ANALYSIS OF REGIONAL LEADING SECTORS AS A BASIS FOR DETAILED SPATIAL PLANNING (RDTR) WEST SUMBA REGENCY - Gill Kodo; fransina w Ballo; olivia l. Eunike tomasowa (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze the structure and classification of economic sectors in West Sumba Regency, examine the utilization of leading sectors as a basis for the preparation of the Detailed Spatial Planning (RDTR), and formulate policy directions for the development of leading sectors in supporting regional spatial planning. The study employed a quantitative descriptive approach using the Klassen Typology analysis method based on sectoral growth rates and contributions to the Gross Regional Domestic Product (GRDP). The data used consisted of secondary data, including the GRDP of West Sumba Regency for the period 2020–2024, RPJMD, RKPD, RPJPD documents, and regional regulations related to regional development. The results indicate that the economic structure of West Sumba Regency is still dominated by the agriculture, forestry, and fisheries sector. However, several leading sectors possess significant potential to drive regional economic growth, including wholesale and retail trade, manufacturing industry, financial and insurance services, real estate, and educational services. Based on the Klassen Typology analysis, the economic sectors in West Sumba Regency are classified into four categories, namely advanced and rapidly growing sectors, advanced but depressed sectors, developing sectors, and relatively underdeveloped sectors. The findings also reveal that the utilization of leading sector analysis can serve as a foundation for the preparation of the RDTR through the determination of regional development zones, strengthening economic growth centers, and spatial allocation aligned with regional characteristics and economic potential. Therefore, policy directions for the development of leading sectors should focus on strengthening regional infrastructure, increasing investment, developing human resources, and optimizing local potential sustainably in order to support more effective, well-directed, and locally based regional development in West Sumba Regency. Keywords: Leading Sectors, Klassen Typology, RDTR, Regional Economic Development, Spatial Planning.